Indonesian Land Rights and Development - Gold, Martin E.; Zuckerman, Russell B. (Columbia Journal of Asian Law, 2014)
Indonesia’s traditional land tenure system, called adat, satisfied the needs of many generations, but did not provide certainty or formal legal relationships conducive to development. The post-independence government has sought to mold the existing system into a more modern form that would better aid its development and has at the same time, sought to maintain control over the country’s natural resources, each to the disadvantage of local communities. The agrarian reforms that were passed created a dual system of law, and resulted in conflict between traditional rights and the modern, western-influenced, interests and purposes of the state. The lack of title registration has been a continuing impediment: the complex procedures, the time, and the cost of securing registered title has been beyond the capacity of many landowners. In dealing with the mix of laws and customary rights and the lack of clear titles, it is the practice of lenders to give a small level of value to land as collateral, not nearly as much credit as would be given in a more modern system. Character counts more than collateral for land users seeking financing. But registration is now coming. The new, technologically advanced, mobile LARASITA registration system recently created, is an important innovative step that is moving the country in a positive direction.* We begin, in Sections I and II, with a brief discussion of the current political structure in Indonesia and of Dutch and British rule. Section III looks at the customary law, called adat, and how it has been affected by Islamic law and European rule. Sections IV and V provide an overview of the central tenants of the Basic Agrarian Law Number 5 of 1960, the centerpiece of the national legal effort to modernize the adat land tenure system. Section VI focuses on the national government’s use of the Basic Forestry Law of 1967 to classify over 69% of the nation’s land as forest. This has the effect of frustrating the ability of local adat communities to farm large swaths of land. The Indonesian land titling system is discussed in Section VII. Section VIII focuses on important regional variations in adat and land titling and juxtaposes two regional variants – that of the Dayak people of Kalimantan, with their relatively less modern system, and the heavily sharia oriented system in Aceh. Section IX discusses the importance of land titling for access to financing. Then Section X looks at the new LARASITA land registration system, which, with its modern tools and thinking, is dramatically increasing land registration in substantial parts of the country. * The original form of this article was done as part of the Sidley Austin LLP Africa-Asia Agricultural Enterprise Pro Bono Program. The Sidley Austin program provides free legal support to small and medium sized agricultural-related enterprises and developmental non-governmental organizations in Africa and Asia. See http://www.sidley.com/Africa-Asia-Agricultural-Enterprise-Pro-Bono-Program/.